Species distribution models describe spatial variability in mesopelagic fish abundance in the Southern Ocean - Woods, Briannyn L.; Van de Putte, Anton P.; Hindell, Mark A.; Raymond, Ben; Saunders, Ryan A.; Walters, Andrea; Trebilco, Rowan (Frontiers in Marine Science, 2023)
Introduction Mesopelagic fishes play a central role in the transfer of energy through open-ocean food webs, particularly in the Southern Ocean where they are both important predators of zooplankton and a key prey group for many higher predators. However, they are notoriously difficult to sample, which has limited our understanding of the bio-physical predictors of their abundance and spatiotemporal variability. Species distribution models can be used to help understand species’ ecological requirements by relating records of their presence or abundance to environmental data. Methods Here, we used data from Myctobase – a new circumpolar database of mesopelagic fishes – to model patterns in abundance of eight key myctophid species (family Myctophidae) and the genus Bathylagus in the Southern Ocean south of 45°S. We developed species-specific boosted regression tree models to obtain circumpolar predictions of abundance. Average daytime and night-time summer predictions for the period 1997 to 2011 at 0 to 200m depths were generated for each species. Results Depth and solar position were important predictors and species were stratified in their depth distribution. For all species, except for G. nicholsi, there was an interaction between depth of capture and solar position, reflecting diel vertical migration. Other important variables included sea surface temperature, dissolved oxygen at 200 m, chlorophyll a, and sea surface height, indicating an association with water mass properties. Circumpolar patterns of abundance varied between species with some displaying affinities for oceanic regions at Antarctic latitudes (e.g., E. antarctica and Bathylagus spp.) or sub-Antarctic latitudes (e.g., K. anderssoni and P. tenisoni); and affinities for shelf regions (e.g., P. boliniand G. nicholsi). Discussion Our findings suggest that the abundance of mesopelagic fish is influenced by diel vertical migration and meso- and sub-mesoscale oceanographic features, with the Polar Front being a major delimiting feature. Our study showed contrasting patterns in community composition with higher species diversity north of the Polar Front that might be indicative of latitudinal variability in food web structure. Our spatial analysis is an important step toward resolving what determines important habitat for mesopelagic fishes, providing foundational information for understanding shifting food web dynamics into the future.